2008
DOI: 10.1016/j.jpainsymman.2007.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Family Members' Perceived Needs for Bereavement Follow-Up

Abstract: Palliative care does not end with the death of the patient, and many palliative care services offer specific follow-up services for the bereaved. The aims of this study were to quantitate perceived bereavement needs and to qualitatively describe these needs. The study design was cross-sectional and targeted family members three to nine months after the patient's death. Two hundred and forty-eight family members responded (response rate 66%) to a postal questionnaire with Likert-type and open-ended questions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
2
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 43 publications
6
72
2
10
Order By: Relevance
“…Participation rate in this study was 77%, which must be considered satisfactory compared to other bereavement studies [5,6,20]. The response rate dropped to 51% after 18 months, which is not uncommon in longitudinal studies, but consequently, interpretation of the analysis needs to be done with caution.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 54%
“…Participation rate in this study was 77%, which must be considered satisfactory compared to other bereavement studies [5,6,20]. The response rate dropped to 51% after 18 months, which is not uncommon in longitudinal studies, but consequently, interpretation of the analysis needs to be done with caution.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 54%
“…Milberg et al [25] attempted to evaluate the experience of caregivers participating in this kind of program. The authors concluded that programs can often motivate feelings of insecurity, because when a caregiver decides to participate, he/she initially feels fear of not being able to identify with the other members of the group, which can cause stress.…”
Section: Discussionmentioning
confidence: 99%
“…questions raised by family members of dying patients [39,46]. In addition, there seems to be both a need among bereaved to talk with staff members about existential issues [35], and a relationship between stress among health care staff caring for dying patients and encounters with such issues [5,12]. Moreover, resilience and well-being in palliative care staff seem to be influenced by their awareness of their own spirituality and existential needs, and such an awareness also helps the nurses to address the needs of their patients and their families [1].…”
Section: How To Provide Support For Staff Members Performing Bereavemmentioning
confidence: 99%
“…In one of our previous studies, 46% (n=248; response rate 66%) of the family members of a deceased patient expressed a need for bereavement follow-up, and 61 % of the respondents favored an individual visit, preferably in their own home, with the staff member who had had the most contact with the patient and the family. The follow-up procedure made the family member experience a feeling of being recognized as a person with his/her own needs, and it was valuable to talk to the staff member about the family member's feelings of guilt [35]. In addition, in Kaunonen et al's study 72% of the bereaved family members that had received a supportive telephone call four weeks after the death reported that the nurse's phone call had an impact on how they perceived the death [26].…”
Section: Introductionmentioning
confidence: 99%